2003
DOI: 10.1111/j.0042-9007.2003.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

First comparison of productivity and citrate donor load between the Trima® version 4 (dual‐stage filler) and the Trima Accel® (single‐stage filler) in the same donors

Abstract: These data show that the Trima Accel represents a further improvement in apheresis platelet production with a better productivity and donor comfort, especially regarding the mean flow of ACDA to the donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 31 publications
6
37
1
Order By: Relevance
“…This was attained by performing all collections using the same staff and donors as well as similar definitions and target endpoints on each instrument. Confirming previous reports [16,21,25], PLT loss was lowest with TA and highest with AM. The latter, however, returned additional saline solution that could have caused higher dilution of the donors' peripheral blood, thus mimicking an increased PLT loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was attained by performing all collections using the same staff and donors as well as similar definitions and target endpoints on each instrument. Confirming previous reports [16,21,25], PLT loss was lowest with TA and highest with AM. The latter, however, returned additional saline solution that could have caused higher dilution of the donors' peripheral blood, thus mimicking an increased PLT loss.…”
Section: Discussionsupporting
confidence: 91%
“…Main characteristics and technical features of the PLT apheresis systems used in this study are described in more detail elsewhere in the literature [16][17][18][19][20][21]. MCS+ was the only device operating a discontinuous separation technique, while all other instruments were continuous operating systems.…”
Section: Platelet Apheresis Systemsmentioning
confidence: 99%
“…The hyperconcentration may have resulted in platelet damage, and therefore we evaluated the Trima system, which uses a different collection system and hyperconcentration method. 8,12,13 Unfortunately, there were no differences in poststorage platelet viability regardless of the Terumo BCT system that was used (Tables 1 and 3; Figure 1A-B).…”
Section: Discussionmentioning
confidence: 96%
“…7 The Trima has a single-stage channel where the cells separate into layers according to specific gravity, and each component leaves by its own outlet into a storage bag. 7,8 All collections were within the manufacturer's bag parameters for volume and total platelets per bag for 5-to 7-day plasma storage. However, these guidelines may not be applicable to the Plasmalyte (Baxter, Deerfield, IL) extended storage studies reported here.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation